A Practitioner's Handbook for Eco-Industrial Parks : Toolbox - United Nations Industrial Development Organization; World Bank Group; Deutsche Gesellschaft für Internationale Zusammenarbeit; Ministry of Trade, Industry and Energy of the Republic of Korea (World Bank, Washington, DC, 2019)
The Eco-Industrial Park (EIP) Practitioner's Handbook is a practical, step-by-step guide that takes stakeholders through the entire process of operationalizing the International EIP Framework. It is composed of three sections. Section one highlights ways in which the government and other relevant stakeholders can support industrial park developers and operators in adopting the International EIP Framework through institutional, financial and technical support. It presents a detailed explanation of the four key steps, as well as a range of activities involved in developing and implementing a national-level EIP initiative. Section two lays out four key steps and action items involved in implementing the International EIP Framework. Section three provides a guideline on how to identify and actively create industrial symbiosis networks-an important strategy for promoting EIPs and operationalizing the International EIP Framework.